Proceedings - 30. Workshop Computational Intelligence : Berlin, 26. - 27. November 2020 - Schulte, Horst; Hoffmann, Frank; Mikut, Ralf (KIT Scientific Publishing, 2020)
The proceedings of the 30th workshop on computational intelligence focus on methods, applications, and tools for fuzzy systems, artificial neural networks, deep learning, system identification, and data mining techniques.